1999
DOI: 10.1016/s0886-3350(99)00009-7
|View full text |Cite
|
Sign up to set email alerts
|

Degeneration and transdifferentiation of human lens epithelial cells in nuclear and anterior polar cataracts

Abstract: Lens epithelial cells in different types of cataracts have distinct cellular characteristics and may possess a bipotential nature with the ability to transdifferentiate into mesenchymal cells. This may be an underlying mechanism for the development of cataract and capsule opacification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
27
0
5

Year Published

2000
2000
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 17 publications
4
27
0
5
Order By: Relevance
“…Many of the markers that are altered in LEC by TGF ␤ are similarly altered in human ASC. Immunohistochemical studies of ASC samples collected at surgery have highlighted the presence of ␣ -smooth muscle actin, vimentin, collagens (types I, III and IV), fi bronectin, tenascin, laminin, and various integrins [Hatae et al, 1993;Schmitt-Graf et al, 1990;Saika et al, 1998;Joo et al, 1999;Lee and Joo, 1999;Zhang et al, 2000;Colitz et al, 2000;Wunderlich et al, 2000;Yoshino et al, 2001;Marcantonio et al, 2003]. Interestingly, the TGF ␤ -inducible gene betaIG-h3 is also upregulated in ASC [Lee et al, 2000].…”
Section: Tgf ␤ -Induced Emt: a Model Of Anterior Subcapsular Cataractmentioning
confidence: 99%
“…Many of the markers that are altered in LEC by TGF ␤ are similarly altered in human ASC. Immunohistochemical studies of ASC samples collected at surgery have highlighted the presence of ␣ -smooth muscle actin, vimentin, collagens (types I, III and IV), fi bronectin, tenascin, laminin, and various integrins [Hatae et al, 1993;Schmitt-Graf et al, 1990;Saika et al, 1998;Joo et al, 1999;Lee and Joo, 1999;Zhang et al, 2000;Colitz et al, 2000;Wunderlich et al, 2000;Yoshino et al, 2001;Marcantonio et al, 2003]. Interestingly, the TGF ␤ -inducible gene betaIG-h3 is also upregulated in ASC [Lee et al, 2000].…”
Section: Tgf ␤ -Induced Emt: a Model Of Anterior Subcapsular Cataractmentioning
confidence: 99%
“…Morphological studies of the anterior lens capsule and lens epithelium have found different changes in their ultrastructure in age-related nuclear cataracts [10,[17][18][19] . The epithelium can become multilayered [17,19] .…”
mentioning
confidence: 99%
“…A mix of both normal and altered epithelial cells is typically observed [11] . The cells can be pleomorphic and degenerated [18,19] , containing pleomorphic nuclei [17] , intracellular vacuoles [9,20,21] and condensed nuclear chromatin [18] . Intercellular spaces can occur between epithelial cells [10,18,22] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously reported that TGF-␤ 1 enhances extracellular matrix production, such as, fibronectin, type I collagen, and the ␣-SMA protein of lens epithelial explants (7). Recent transgenic studies using the dominant negative-TGF-␤ receptor approach have shown that TGF-␤ plays an important role in the normal maturation and survival of lens fiber cells (33).…”
mentioning
confidence: 99%